Doing critical research - Alvesson, Mats, 1956-; Deetz, Stanley A. (London : SAGE Publications Ltd, 2021)
In the 20 years since its publication, Mats Alvesson's seminal book Doing Critical Management Research has sold over 3000 copies. Mats Alvesson is considered a founder of Critical Management Studies, and has an unrivalled reputation in this field. As the book is now quite dated, Mats is keen to update the text and broaden its scope so that it is relevant for all of the social sciences, and not just management. The new title, Doing Critical Research, will be marketed as a first edition, but the copy will make it clear it is based on Doing Critical Management Research to avoid any confusion.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Management -- Research -- Methodology